THE IMPORTANCE OF AFFECT IN LANGUAGE LEARNING - Arnold, Jane (Neofilolog, 2019)
As language teachers, we have to pay attention to many things in our work but cognitive aspects of foreign or second language learning cannot provide all the information we need. If we also give attention to the affective domain, this can make our teaching more effective. In this article we will be considering some of the affective factors and exploring how they influence the process of language learning. Special emphasis will be placed on implications for teachers in the classroom.